Performance analysis on a bidirectional operation of a three-level hybrid ANPC inverter - Kwon, Bong Hyun; Kim, Sang Hun; Bae, Kyu Chul; Lee, Kyo Beum (Transactions of the Korean Institute of Electrical Engineers, 2019)
This paper analyzes the performance of a three-level hybrid active neutral-point clamped (ANPC) inverter in a bidirectional operation. In the bidirectional operation where electrical energy flows from dc source to ac grid and vice versa, a weakness of neutral-point-clamped (NPC) inverter is an unequal loss distribution between four silicon (Si) switching devices. A leg of the hybrid ANPC inverter consists of the four Si insulated gate bipolar transistors (IGBTs) and two silicon carbide (SiC) active switches. Only two SiC metal oxide semiconductor field effect transistors (MOSFETs) take all the switching events using redundant switching states but the switching losses are reduced compared to that of NPC inverter. The hybrid ANPC topology has an advantage of almost the same power loss operating as a grid-connected inverter and rectifier. The validity of the power loss analysis in the bidirectional operation is verified by a PSIM simulation model and experiment in the grid-connected three-phase three-level voltage source inverter.
Keywords: Active neutral point clamped; Bidirectional operation; Grid connected inverters; Performance analysis; Silicon carbides (SiC); Active Neutral-Point-Clamped (ANPC) inverter; Bidirectional operation; Grid connected inverter system; Performance analysis; Silicon Carbide (SiC) switches